Savings in the age of zero interest rate: Some evidence from SEE countries - Ljupka Georgievska (National Bank of the Republic of Macedonia, 2020)
The past decade following the global economic crisis (2008-09) will be certainly marked as the era of historically low interest rates, while the current juncture of COVID-19 pandemic outbreak raises the occasion of another extended period of very low interest rates. Yields have been falling across the whole spectrum of financial assets, including bank deposits, raising the concern of possible negative impact of low interest rates on households' propensity to save. In this analysis, we briefly discuss developments in household savings against the low interest rates environment in the countries from the European Union (EU) and Southeastern Europe (SEE). The aim is to shed some light on the interest rate-savings relationship, observe the potential disruptions to this relation due to the persistently low interest rates and the role that the interest rates played vis-à-vis other factors in shaping households' decisions to save. The analysis points that low interest rates and their dynamics over time have not been a key determinant of saving and investment behavior of households in the region. Factors relating to disposable income and wealth, households' preferences and risk attitudes, as well as institutional frameworks, are likely to have been far more important determinants in this sense. In SEE countries, bank deposits have sustained and further strengthened their role as leading saving instrument in households' financial assets post-crisis, despite the low interest rate environment, while households' saving ratio has improved from very low and even negative levels in some countries pre-crisis.
Keywords: 330; Niedrigzinspolitik; Sparen; EU-Staaten; Südosteuropa